Verification of the Simulation Model Based on the Example of Combined Sewage System in Głogów = Weryfikacja modelu symulacyjnego na przykładzie sieci kanalizacji ogólnospławnej miasta Głogowa - Nowogoński, Ireneusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The verification of simulation model of combined sewage system was presented in article. The model of sewage system functioning in Głogów was developed using SWMM 5.1 (Storm Water Management Model) software. It was calibrated based on the results of field studies from the years 2011-13, while the properness of its activity was verified for the results of measurements carried out in 2014.
Keywords: combined sewage system; rainfall-runoff phenomena; simulation models; kanalizacja ogólnospławna; zjawisko opad-odpływ; modele symulacyjne